2017
DOI: 10.1021/acschembio.7b00641
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Acyl-ACP Thioesterase toward Substrate Specificity Design

Abstract: Acyl-ACP thioesterase (TE) catalyzes the hydrolysis of thioester bonds during type II fatty acid synthesis and directly determines fatty acid chain length. Most TEs are responsible for recognition of 16:0 and 18:1 substrates, while specific TEs interrupt acyl-ACP elongation at C8-C14. However, the acyl selection mechanism of TE has not been thoroughly elucidated to date. In this study, the crystal structure of the C12-specific thioesterase FatB from Umbellularia californica, which consists of two independent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 31 publications
3
63
0
Order By: Relevance
“…Thr137 is located near the bottom of the binding pocket and its bulky side chain restricts binding of acyl chains longer than C 12 , thus making lauric acid (C 12 ) the main product. In contrast, the rationally designed mutant Thr137Gly showed a product spectrum shifted towards longer fatty acids of C 14 –C 16 in length …”
Section: Ks At and Te Domains/enzymes—key Players In Chain‐length Cmentioning
confidence: 83%
See 3 more Smart Citations
“…Thr137 is located near the bottom of the binding pocket and its bulky side chain restricts binding of acyl chains longer than C 12 , thus making lauric acid (C 12 ) the main product. In contrast, the rationally designed mutant Thr137Gly showed a product spectrum shifted towards longer fatty acids of C 14 –C 16 in length …”
Section: Ks At and Te Domains/enzymes—key Players In Chain‐length Cmentioning
confidence: 83%
“…The best‐characterized plant TE is FatB from Umbellularia californica (termed UcFatB), which has been extensively studied for almost three decades . Its X‐ray structure having recently been determined (PDB ID: 5X04) . UcFatB forms a homodimer, each monomer showing a tandem hotdog fold.…”
Section: Ks At and Te Domains/enzymes—key Players In Chain‐length Cmentioning
confidence: 99%
See 2 more Smart Citations
“…1) (Emanuelsson et al 2007). Sequence alignment of the deduced amino acid sequence of CvFatB4 and several plant FatB proteins with known biochemical activities revealed that four amino acid residues (Asp 312 , Asn 314 , His315, and Glu 350 in CvFatB4) are conserved and localized in so-called hot-dog folds, suggesting that they are catalytically important and CvFatB4 catalyzes the hydrolysis of the thioester bond using the catalytic mechanism found in UcFatB (Dani et al 2011;Dörmann et al 1995;Feng et al 2017; Sánchez-García et al 2010).…”
Section: Resultsmentioning
confidence: 99%